Mechanical property strengthening by post-heat treatments in NiTiCu shape memory alloys fabricated by twin-wire arc additive manufacturing - Long Chen; Miao Zhao; Jiehao Wu; J. P. Oliveira; Fissha Biruke Teshome; Bowen Pang; Jiajia Shen; Yiming Wu; Naixun Zhou; Norbert Schell; Zhi Zeng (Virtual and Physical Prototyping)
To address the challenges of wide transformation hysteresis as well as the poor properties of NiTi-based alloys fabricated by twin-wire arc additive manufacturing, post-heat treatments were employed in as-deposited NiTiCu alloys. After aging at 450°C, 550°C, and 650°C, the alloys exhibited significant reduction in the precipitate sizes, narrow transformation hysteresis, uniform distribution of microhardness, and substantial improvement in mechanical properties. With the increase of the aging temperature, the matrix grain size and the precipitate size coarsened, which was detrimental to the resultant mechanical properties. The alloys aged at 450°C exhibited the narrowest transformation hysteresis of 11.7°C and optimal mechanical properties (tensile strength of 539 MPa and fracture strain of 6.9%). The enhancement of mechanical properties can be attributed to the smaller matrix grain size and precipitate size and the higher proportion of high-angle grain boundaries in this material condition. This work provides practical significance for the twin-wire arc additive manufacturing and performance optimisation of NiTi-based ternary alloys.